Socialization of Poetry and Short Stories to Support Student Creativity at SDN 001 and SDN 002 Semurut: Sosialisasi Puisi dan Cerpen Guna Menunjang Kekreatifitasan Siswa di SDN 001 dan SDN 002 Semurut - Kusuma, Ratna; Widyaningrum, Erlyne Nadhilah; Sholikhati, Adrikni; Suyitno (ANDIL Mulawarman Journal of Community Engagement, 2025)
Semurut Village in Tabalar District, Berau Regency, East Kalimantan, has great potential in marine and agricultural resources. However, some students in the village, especially grades 4-6 at SDN 001 and SDN 002, still do not understand poetry and short stories. This study aims to improve students' creativity in writing and thinking creatively through the introduction of poetry and short stories. The method used was a two-stage socialization at SDN 001 on July 29 and at SDN 002 on August 10, involving students in grades 4-6. This activity included an introduction to poetry and short stories, poetry reading practice, and basic writing techniques. The results of the activity showed students' enthusiasm in learning and understanding poetry and short stories, as well as an increase in creative thinking skills. Introduction to poetry and short stories has been proven to be able to stimulate students' creativity and channel their interests and talents in the field of literature.